Sixty Years of Kossel Isoelectronic Series—Arguments Derived from Photo-electron and Atomic Spectra - Christian K. Jørgensen (CHIMIA)
In spite of chemical shifts (in photo-electron spectra) and interatomic relaxation by condensation of gaseous samples, the difference ΔI between the ionization energies of the monatomic entities and the compounds in the oxidation state z tends to be proportional to z. The new parameter (ΔI/z) seems to indicate a superposition of electrostatic interatomic effects and the screening of the inner shell by external electrons. It is suggested to call the number of electrons in a Kossel isoelectronic series K.